Pembatasan Kebebasan Merekam dan Mengambil Gambar Kegiatan Dalam Persidangan Dalam Peraturan Mahkamah Agung Nomor 5 Tahun 2020 Tentang Protokol Persidangan dan Keamanan Dalam Lingkungan Pengadilan - Anton Hariyadi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
The Supreme Court Regulation Number 5 of 2020 concerning Trial Protocols and Security in a Court Environment has created a lot of pros and cons from various perspectives. There are many regulations that allow it as a form of freedom of expression, some are related to human rights violations, fulfillment and protection. In this paper the author uses a qualitative research methodology with legal materials sourced from the Supreme Court Regulation Number 5 of 2020 concerning Trial Protocols and Security in a Court Environment and other laws and regulations, and theories by experts from the literature related to this research. The results of the study state that the importance of implementing regulations regarding freedom of expression through digital media in Indonesia, and the application of Law No.39 of 1999 concerning Human Rights and specifically regulating Information and Electronic Transactions through Law No.11 of 2008.Keywords: Restriction; The judge; Record